AMOUNTS IN THE AUXILIARY BOARDING SCHOOL LEARNING METHODOLOGY (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, Students of auxiliary boarding schools are given information about how to disassemble quantities into units, about parables and arithmetic operations related to quantities, about difficulties in deducing quantities.